Optimization and fabrication of a portable biogas reactor (Journal of Chemical Engineering, 2014)
The study was conducted to investigate the production of biogas from kitchen waste (KW) with co-digestion of cow manure (CM) by using anaerobic digestion process. The experimental protocol was defined to examine the effect of organic loading rate (OLR), temperature, and NaOH-treatment on the efficiency of the production of biogas. A portable biogas reactor was fabricated for efficient biogas production which included an agitation and a heating system. The KW and CM were co-digested at ratios of 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1 and 8:1 respectively at loading rates of 50, 100,150, 200, 250, 300, 350, and 400 g/L. The highest degradation rate of 7.96 ml/g was obtained from the loading rate of 200 g/L. Furthermore, KW was co-digested at different temperatures 25, 35, 40, 45, and 500C, maintaining the same loading rate of 200 g/L and the highest degradation rate of 7.98 ml/g was inspected at temperature 350C. The alkali (NaOH) was used to treat KW to improve biogas production and four NaOH doses 0.5%, 1.0%, 1.5%, and 2.0% on wet matter basis of KW were applied. The highest degradation rate 13.21ml/g was obtained from 1.5% NaOH which was almost double compared to untreated KW. In addition, 39.74 % more biogas could be produced from 1.5% NaOH-treated KW than untreated KW. The results were further verified by scaling up to a semi-continuously-operating pilot-plant reactor co-digesting KW with CM as bacterial seed and confirmed that no negative impact was imposed at optimized conditions. DOI: http://dx.doi.org/10.3329/jce.v27i2.17799 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 2, December 2012: 36-40